Penggunaan Media Video Pembelajaran Terhadap Hasil Belajar IPA Biologi Materi Sistem Pernapasan Manusia di SMP GKST 3 Tentena - Rinty, Ulfa Tridewi Octovianty; Tjenemundan, Delfince; Ambotuo, Viskarita F.M (Program Studi Pendidikan Biologi FKIP Uniiversitas Muhammadiyah Luwuk, 2024)
Abstract: The learning process requires every teacher to create conditions in the learning space so that it can be useful and interesting, which can help students be able to achieve predetermined goals. This research aims to determine students' Biology Science learning outcomes regarding the human respiratory system before and after using learning video media at GKST 3 Tentena Middle School. This research uses a quantitative descriptive approach. The population of this research was 15 students in class VIII The resulting data was analyzed using the t-test technique by explaining and illustrating the data presented in the form of qualitative descriptive tables or graphs. The results of this research show that there are differences in student learning outcomes in the biology science subject material on the human respiratory system for class VIII students at SMP GKST 3 Tentena in using video learning media. This can be seen from the increase in the average pre-test score (22.61) and the average post-test score (48.93). The relationship between the values ??of the two results is moderately correlated, namely a correlation coefficient of 0.5060.